DETERMINAN PENGAJUAN PEMBIAYAAN DI LINGKUNGAN BANK PERKREDITAN RAKYAT JEMBER - Nurhayati, Nurhayati; Meirina, Petty Winda (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract: The abjective of this study is finding whether the customer has the difference between a view of the product financing they take on microfinance institutions of particularinstitution of islamic finance is based on several factors. The study population sare whole customer susefinancing services on financing bank rakyat syariah